A five-year prospective evaluation of anticholinergic cognitive burden and falls in the Malaysian elders longitudinal research (MELoR) study - Xu, Xiang Jiang; Myint, Phyo Kyaw; Kioh, Sheng Hui; Sumaiyah, Mat; Reena, Rajasuriar; Shahrul, Bahyah Kamaruzzaman; Tan, Maw Pin * (Elsevier, 2022)
Background: While anticholinergic use is associated with stroke, dementia and mortality, few have evaluated its potential link with falls. To determine the relationship between anticholinergic cognitive burden (ACB) and falls over five years using the Malaysian Elders Longitudinal Research (MELoR).